Critical Education through DisCrit, LatCrit, and Intersectionality: A Systematic Literature Review on Efforts to Address Social Injustice - Silvianus Gole; Arismunadar Arismunadar; Farida Ohan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to analyze and synthesize the application of critical theories systematically, specifically Disability Critical Race Theory (DisCrit) and Latino Critical Race Theory (LatCrit), as well as the integration of intersectionality theory in education to address social injustice. The method used is a Systematic Literature Review (SLR) by analyzing 23 relevant studies selected based on predetermined inclusion criteria, using articles indexed in the Scopus database published between 2000 and 2022. The results show that DisCrit and LatCrit are effective in creating inclusive learning spaces by addressing race- and disability-based discrimination. In addition, integrating intersectionality theory deepens understanding of students' social experiences influenced by multiple identity factors. This study also found that hope plays an important role in critical education, equipping students with the tools to challenge social injustice and deepen critical awareness. In conclusion, the application of critical theories in education has the potential to strengthen students' social awareness and empower them to participate in social change. This study contributes to the development of a more equitable and inclusive education model and suggests further research that emphasizes teacher training and the long-term impact of critical education.